Symptomatic Internal Carotid Agenesis in Children. (25th April 2020) - Alhaizaey, Abdullah; Alhelali, Ibrahim; Alghamdi, Musaed; Azazy, Ahmed; Samir, Mohammed A.
Abstract : Carotid artery agenesis is a rare congenital anomaly, and there are controversies in the leading cause for it. We present a 6-year-old girl with resolved focal neurological ischemic stroke that showed bilateral internal carotid artery (ICA) agenesis. Through this paper, we highlight the carotid canal congenital obliteration hypothesis as it may be a risk for such finding.